Dental care provision by students on a remote rural clinical placement - Ratilal Lalloo; Jane L. Evans; Newell W. Johnson (Elsevier, 2013)
Abstract Background: In 2009, the School of Dentistry and Oral Health, Griffith University, commenced a clinical placement in a remote rural and Indigenous community in Australia. This paper analyses the type of treatment services provided from 2009 to 2011 by year, type of patient and age of patient. Methods: All treatment data provided were captured electronically using the Australian Dental Association (ADA) treatment codes. Audited reports were analysed and services categorised into six broad treatment types: consultation, diagnostic, preventive, periodontics, oral surgery and restorative services. Results: The bulk of dental care episodes provided over the three‐year period were for clinical examinations, restorative and oral surgery services. Preventive and periodontic services generally comprised less than 10% of the care provided. Over time fewer clinical examinations were conducted and restorative dentistry increased in the second and third years of the placement. There were no significant differences in the types of care provided to public and private patients. Conclusion: Clinical placement of final‐year dental students in remote rural settings has helped address a largely unmet dental need in these regions. Implications: Dental student clinical placement is effective in providing care to communities in a remote rural setting. Student placements are, however, only able to deliver dental care in few remote rural communities, and therefore will make a negligible impact on the level of untreated dental disease in the short term. It is hoped that the experience will lead to more graduates serving some of their professional lives in remote communities.